Examining Small-Town Growth and Expansion in Peri-urban Areas of Small Cities: Evidence from Peripheries of Three Small Cities in Central Java - Fadjar Hari Mardiansjah; Agung Sugiri; Samsul Ma'rif (The Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Urbanization in small and medium-sized cities in Java is marked by an urban expansion process to the surrounding areas, forming the growing small towns in their peripheries. Using the case of the extended urban areas of Tegal, Pekalongan and Magelang in Central Java, this study examined small-town growth and development in peri-urban areas of small and medium cities. It first looked at the growth of small towns in the peri-urban areas of these small cities and then identified various factors and mechanisms that contribute to the formation, growth and expansion of small towns. The study further looked into the challenges and implications of the trend toward policies for managing such processes more sustainably. The growth of urbanized villages in some kabupatens (non-urban districts or regencies) surrounding these small cities, as documented by the national statistical board from 1990 to 2017, was used as the basis for analyzing these factors. This paper concludes with a discussion on the challenges and policy implications for growing small towns. The findings of this study can be useful for formulating a better approach to managing urbanization processes in the future. Abstrak. Urbanisasi kota-kota kecil dan menengah di Jawa ditandai dengan proses perluasan kota ke wilayah sekitarnya, membentuk kota-kota kecil yang berkembang di pinggirannya. Dengan menggunakan kasus perluasan wilayah Tegal, Pekalongan dan Magelang di Jawa Tengah, penelitian ini mengkaji pertumbuhan dan perkembangan kota kecil di wilayah pinggiran kota kecil dan menengah. Ini pertama-tama melihat pertumbuhan kota-kota kecil di daerah pinggiran kota-kota kecil ini dan kemudian mengidentifikasi berbagai faktor dan mekanisme yang berkontribusi pada pembentukan, pertumbuhan, dan perluasan kota-kota kecil. Studi ini lebih jauh melihat tantangan dan implikasi dari tren terhadap kebijakan untuk mengelola proses tersebut secara lebih berkelanjutan. Pertumbuhan desa urban di beberapa kabupaten (kabupaten atau kabupaten non-urban) di sekitar kota-kota kecil tersebut, sebagaimana didokumentasikan oleh BPS (Badan Pusat Statistik) dari tahun 1990 hingga 2017, digunakan sebagai dasar untuk menganalisis faktor-faktor tersebut. Makalah ini diakhiri dengan diskusi tentang tantangan dan implikasi kebijakan untuk pertumbuhan kota-kota kecil. Temuan studi ini dapat berguna untuk merumuskan pendekatan yang lebih baik untuk mengelola proses urbanisasi di masa depan. Kata kunci. Jawa Tengah, kota kecil, urbanisasi, ekspansi kota.